2011
DOI: 10.1159/000328890
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for Glomus Jugulare and Tympanicum

Abstract: Objective: To establish the role of gamma knife radiosurgery (GKS) as a treatment strategy for glomus jugulare and tympanicum. Method: A retrospective review of 14 glomus tumors, including 11 glomus jugulare and 3 glomus tympanicum tumors, which were treated by GKS in Taipei Veterans General Hospital from 1993 to 2009, was conducted. Two of these cases had undergone prior surgery with partial tumor resection, and the other 12 cases received primary treatment with GKS after a thorough neuroimaging and cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 85 publications
2
21
0
1
Order By: Relevance
“…In general, patients either maintain function of their cranial nerves or have improvement in their dysfunction after treatment but many of these studies included patients treated with multiple types of surgical and/or radiation treatment types. 6,12,13,2226 Our study demonstrated overall stability of cranial nerve function using single modality GKRS. Those with lower cranial neuropathies were rehabilitated well (i.e.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In general, patients either maintain function of their cranial nerves or have improvement in their dysfunction after treatment but many of these studies included patients treated with multiple types of surgical and/or radiation treatment types. 6,12,13,2226 Our study demonstrated overall stability of cranial nerve function using single modality GKRS. Those with lower cranial neuropathies were rehabilitated well (i.e.…”
Section: Discussionsupporting
confidence: 51%
“…On average, the decrease in size of tumors treated in our study was 37% is comparable to other centers that have studied tumor response to GKRS. 9,12,17,2125 These are slow growing tumors and it is important to follow these tumors over longer periods of time to assess for control of growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al showed local control rates of 100% (n = 14/14) after gamma knife radiosurgery. All patients had a significant tumor regression with a median volume reduction of 34.0% [33]. The authors concluded that radiosurgery is a good alternative to a microsurgical resection of these lesions.…”
Section: Skull Base Tumorsmentioning
confidence: 88%
“…Though surgery has been the traditional treatment of choice for TMPs, suggestions of radiation as a primary alternative to surgery appear every now and then in literature [19][20][21][22]. We firmly believe that radiation has no role in the primary treatment of TMPs and this view has also been emphasized by many authors [10,19,23].…”
Section: Rt and Wait-and-scan As A Treatment Optionmentioning
confidence: 98%